In India, Returns to Education: A Review (International Journal of Innovative Research in Engineering & Management, 2023)
In this article, a critical assessment of  some of the most significant studies on rates of return to  education in India is presented, emphasizing the  differences in calculation techniques, assumptions, and  modifications used, as well as the conclusions reached. the human investment revolution in economic thought has yet  to take root in the minds of Indian educational  policymakers. India invests about 3% of its GNP in its  massive formal educational enterprise, which has over 200  million students on rolls and about 3 million teachers  spread across 124 universities, over 5,000 colleges, and  750 thousand schools. The ramifications of their findings  are also considered. Conclusions on the efficacy of  investment in education in India are made based on this  review. Theoretical and empirical issues that emerge in  this setting are discussed, and the potential for future study  in this field is also considered.
Keywords: Children Education; Engineering Education; Five Year Plan; Indian Education; Third World Country